Digital Image and Video Watermarking and Steganography - Ramakrishnan, Sudhakar (IntechOpen, 2019)
Authenticating data such as image, video, and audio is an important task in digital communication. Another critical task is establishing ownership of the copyright. Digital watermarking is a technique used to provide authentication and ownership of the copyright to the data. Too much digitalization of data in the form of image, video, and audio communicated through various web and mobile applications makes authentication a challenging task. Steganography, the art of hiding tiny pieces of data in image, video, and audio, can also help in copyright protection, authentication, and access control. This book provides three watermarking and two steganography methods and will be a useful resource for graduate students, researchers, and practicing engineers in the field of electrical engineering.